Effects of microplastics on soil microorganisms and microbial functions in nutrients and carbon cycling – A review - Aralappanavar, Vijay Kumar; Mukhopadhyay, Raj; Yongxiang, Xu; Jingnan, Liu; Bhatnagar, Amit; Praveena, Sarva Mangala; Yang, Li; Paller, Mike; Adyel, Tanveer M.; Rinklebe, Jörg; Bolan, Nanthi S.; Sarkar, Binoy (Elsevier B.V., 2024)
The harmful effects of microplastics (MPs) pollution in the soil ecosystem have drawn global attention in recent years. This paper critically reviews the effects of MPs on soil microbial diversity and functions in relation to nutrients and carbon cycling. Reports suggested that both plastisphere (MP-microbe consortium) and MP-contaminated soils had distinct and lower microbial diversity than that of non-contaminated soils. Alteration in soil physicochemical properties and microbial interactions within the plastisphere facilitated the enrichment of plastic-degrading microorganisms, including those involved in carbon (C) and nutrient cycling. MPs conferred a significant increase in the relative abundance of soil nitrogen (N)-fixing and phosphorus (P)-solubilizing bacteria, while decreased the abundance of soil nitrifiers and ammonia oxidisers. Depending on soil types, MPs increased bioavailable N and P contents and nitrous oxide emission in some instances. Furthermore, MPs regulated soil microbial functional activities owing to the combined toxicity of organic and inorganic contaminants derived from MPs and contaminants frequently encountered in the soil environment. However, a thorough understanding of the interactions among soil microorganisms, MPs and other contaminants still needs to develop. Since currently available reports are mostly based on short-term laboratory experiments, field investigations are needed to assess the long-term impact of MPs (at environmentally relevant concentration) on soil microorganisms and their functions under different soil types and agro-climatic conditions.